2021
DOI: 10.1016/j.imr.2020.100680
|View full text |Cite
|
Sign up to set email alerts
|

Moxibustion for cognitive impairment: A systematic review and meta-analysis of animal studies

Abstract: Background Cognitive impairment is an age-dependent chronic disorder that exponentially worsens with age; however, its treatment is mostly symptomatic. Moxibustion is widely accepted in East Asia as a treatment for cognitive impairment. This systematic review aimed to verify the efficacy and underlying mechanism of moxibustion in treating cognitive impairment. Methods Sixteen trials involving 324 animals obtained from MEDLINE (PubMed), EMBASE, the Cochrane library, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
(38 reference statements)
0
10
0
Order By: Relevance
“…According to previous studies on the treatment of cognitive disorders with moxibustion (Aum et al, 2021 ), we selected six acupoints including Guanyuan, Baihui, bilateral Xuanzhong, and bilateral Zusanli in the MCI group. All MCI patients were treated with moxibustion by the same acupuncturist.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to previous studies on the treatment of cognitive disorders with moxibustion (Aum et al, 2021 ), we selected six acupoints including Guanyuan, Baihui, bilateral Xuanzhong, and bilateral Zusanli in the MCI group. All MCI patients were treated with moxibustion by the same acupuncturist.…”
Section: Methodsmentioning
confidence: 99%
“…Moxibustion is a treatment that uses the heat generated by burning moxa sticks to stimulate acupoints, producing a central nervous system regulation similar to acupuncture (Bao et al, 2016 ). It is a commonly accepted treatment approach for cognitive impairment in East Asia (Aum et al, 2021 ), with the advantages of painlessness, ease of operation, and fewer adverse events. A systematic review showed that moxibustion could participate in inhibiting oxidative stress and cell apoptosis, adjusting inflammation and Aβ genesis activation of vascular endothelial growth factor, and regulating the metabolic products in the tricarboxylic acid cycle and fatty acid metabolism (Aum et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data generated while working on a previous SR were used to train and validate the model. Two different tasks were tested for the two types of datasets [20][21][22][23][24][25]: datasetA with 3,268 articles [25,26] and datasetB with 409 case studies. The first task was to classify the included articles using datasetA and its adjusted version, whose class composition was adjusted from a ratio of 9.08:1 to 2.45:1 by generating dummy data.…”
Section: Methodsmentioning
confidence: 99%
“…To train the proposed algorithm, we used two types of datasets comprising documents that had been collected during SRs performed in previous works [19][20][21][22][23][24]. Data-setA comprises 3268 articles retrieved for the theme of "moxibustion for improving cognitive impairment" [24,25]. The first task using datasetA was to classify the included articles that satisfy the three theme criteria: (1) cognitive impairment as the target disease, (2) moxibustion therapy as the intervention, and (3) experimental design using animal models.…”
Section: Datasetsmentioning
confidence: 99%